Synthesis and structure of some new Schiff bases, derivatives of 2-((4-((R-benzylidene)amino)-5-(2-fluorophenyl)-4H-1,2,4-triazole-3-yl)thio)acetohydrazides - Ye. S. Pruglo (Zaporozhye State Medical University, 2018)
Triazole derivatives are among wide range of pharmacological agents, such as antimicrobial, analgesic, anti-inflammatory, anticonvulsant, antitumor, antimalarial, antiviral, antiproliferative, anti-cancer drugs etc. The importance of triazole derivatives is in their various biological properties. That is why they have a good position in heterocyclic chemistry. The purpose of this work was to synthesize and define physical and chemical parameters of new 2-((4-((R-benzylidene)amino)-5-(2-fluorophenyl)-4H-1,2,4-triazole-3-yl)thio)acetohydrazide derivatives. Material and methods. Studying of physical and chemical properties of synthesized compounds was carried out in accordance with the methods of the State Pharmacopoeia of Ukraine. The melting temperature of the synthesized compounds was set on the automatic device for determining the melting temperature MPA100. The Elementar Vario L cube element element analyzer was used to determine the elemental composition of the synthesized substances. 1H NMR spectra of compounds were recorded using a Varian Mercury VX-200 spectrometer (1H, 200 MHz), solvent DMSO-d6, internal standard tetramethylsilane (TMS). Results. 2-((4-((R-benzylidene)amino)-5-(2-fluorophenyl)-4H-1,2,4-triazole-3-yl)thio)acetohydrazides (1a-c) were used as initial materials. These compounds were obtained by reaction of hydrazine hydrate 1.5 molar excess with the corresponding 2-((4-((4-R-benzylidene)amino)-5-(2-fluorophenyl)-4H-1,2,4-triazole-3-yl)thio)acetic acid. Subsequently, corresponding R'-benzaldehyde was added to the synthesized products 1 a-c in the mixture of acetic acid-isopropyl alcohol (2: 1) and heated for 30 minutes, after which the final product was isolated after 6-8 hours. Conclusions. As a result of the research 18 new 2-((4-((R-benzylidene)amino)-5-(2-fluorophenyl)-4H-1,2,4-triazole-3-yl)thio)acetohydrazides (1a-c) and their R'-N-benzylidene-2-((4-((4-R-benzylidene)amino)-5-(2-fluorophenyl)-4H-1,2,4-triazole-3-yl)thio)acetohydrazides (2a-e, 3a-h, 4a, 4b) were synthesized. The structure of the obtained substances was confirmed by the data of elemental analysis, 1H NMR spectroscopy.